2020
DOI: 10.32872/cpe.v2i2.2947
|View full text |Cite
|
Sign up to set email alerts
|

Change processes in cognitive therapy for social anxiety disorder delivered in routine clinical practice

Abstract: Background Most studies examining processes of change in psychological therapy for social anxiety disorder (SAD) have analysed data from randomised controlled trials in research settings. Method To assess whether these findings are representative of routine clinical practice, we analysed audit data from two samples of patients who received Cognitive Therapy for SAD (total N = 271). Three process variables (self-focused attention, negative social cognition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
1
7
0
2
Order By: Relevance
“…Significant reverse mediation was also shown for all but one (SCQ belief) of these variables, and strong mediation effects were observed in this direction, suggesting a cyclical relationship. These findings are consistent with those of a recent study examining processes of change in CT-SAD delivered face-to-face ( Thew et al, 2020 ). Although baseline scores on the mediator and outcome variables were accounted for in these models, it is possible that the strength of the present mediation effects may be underestimated given that much of the overall change on these variables occurred prior to the midpoint assessment.…”
Section: Discussionsupporting
confidence: 92%
“…Significant reverse mediation was also shown for all but one (SCQ belief) of these variables, and strong mediation effects were observed in this direction, suggesting a cyclical relationship. These findings are consistent with those of a recent study examining processes of change in CT-SAD delivered face-to-face ( Thew et al, 2020 ). Although baseline scores on the mediator and outcome variables were accounted for in these models, it is possible that the strength of the present mediation effects may be underestimated given that much of the overall change on these variables occurred prior to the midpoint assessment.…”
Section: Discussionsupporting
confidence: 92%
“…Hasil ini mendukung penelitian sebelumnya, yang menemukan bahwa terapi kognitif dapat mengubah kecemasan yang disebabkan pemikiran-pemikiran negatif pada wanita yang mengalami premenopouse (Afradipta, 2021). Berbagai penelitian juga menunjukkan hasil positif dalam pemberian terapi kognitif dalam mengatasi kecemasan terkait situasi sosial (Stangier et al, 2003) (Thew et al, 2020;Warnock-Parkes et al, 2020).…”
Section: Pembahasanunclassified
“…Selain itu, intervensi dengan pendekatan kognitif menunjukkan hasil yang lebih baik (Warnock-Parkes et al, 2020). Berbagai penelitian menunjukkan terapi kognitif yang diberikan secara individual kepada subjek dapat efektif untuk mengatasi kecemasan terkait situasi sosial (Stangier et al, 2003;Thew et al, 2020;Warnock-Parkes et al, 2020). Terapi kognitif juga menunjukan keefektifan dalam mengatasi kecemasan sosial pada remaja (Leigh & Clark, 2016).…”
unclassified
“…Thus, the main goal in Clark’s cognitive model is helping patients to develop awareness of biased cognitive processes and to correct them. There is indeed a small but growing number of process studies in CBT for SAD, and most of them found that improvements in negative cognitions, threat appraisals, self-focused attention, anticipatory processing, post-event rumination, and avoidance were associated with improved outcomes [ 97 ].…”
Section: The Process Of Change In Eft For Social Anxietymentioning
confidence: 99%